Constitucionalidad de las medidas de amparo, contempladas en el artículo 13 de la ley 103, dictadas en los casos de violencia intrafamiliar. - Chica Miñán, Néstor Emiliano (2013)
Through the thesis will be achieved reform the protection measures prescribed by law against violence to women and the family, guaranteed the effective enjoyment of the right to physical, mental, sexual freedom of women integrity and equal rights and respect for human dignity, which hinders the participation of women in the same conditions as men in all aspects of life.